Effect of Meconium on the Contractility of the Superior Mesenteric Artery: A Clue to Intestinal Damage in Gastroschisis - Karakuş, Osman Z.; Solmaz, Bora; Ateş, Oğuz; Ateş, Mehmet; Hakgüder, Gülce; Olguner, Mustafa; Akgür, Feza M. (European Journal of Pediatric Surgery, 2015)
Introduction Intestinal damage has been shown to occur when intra-amniotic meconium concentration exceeds threshold level. However, the mechanism of the meconium-induced intestinal damage is still unclear. Intestinal ischemia can cause intestinal damage in gastroschisis. This study was aimed to determine the effects of intra-amniotic meconium on the contractility of superior mesenteric artery (SMA).Materials and Methods Eighteen-day-old fertilized chick embryos (Gallus Domesticus) were extirpated and intestines were harvested. The SMA specimens were prepared as 4 mm segments in the organ bath with Krebs–Henseleit buffer. The isometric contraction responses of the SMA specimens were evaluated with norepinephrine, different meconium concentrations, and clear amniotic fluid. Maximum isometric contractions responses (MICR) of the SMA specimens were recorded with an amplifier system on a computer.Results In the norepinephrine group, MICR was found as 2.92 ± 0.57 mN. While MICR of the 1/100 meconium group (highest meconium concentration) was found as 1.56 ± 0.40 mN, MICR of the clear amniotic fluid group was 0.41 ± 0.07 mN. The MICR of the norepinephrine group was significantly increased compared with the 1/100 meconium and clear amniotic fluid groups. MICR of the 1/100 meconium group was also found to be significantly increased compared with clear amniotic fluid group. No statistically significant difference was found among the meconium subgroups.Conclusion Intra-amniotic meconium in fetuses with gastroschisis might cause ischemic intestinal damage by reducing the intestinal blood flow. Further studies are needed to show the outcomes of the vasoactive effect of meconium on the SMA blood flow.
Keywords: gastroschisis; superior mesenteric artery; contractility; intestinal damage; meconium